Social Acceptance and Rejection among Teenagers as seen in Jerry Spinelli’s Novel entitled Stargirl - Mantik, Valencia; Liando, Nihta V. F; Sabudu, Delli (Program Studi Pendidikan Bahasa Inggris, 2025)
This study explored the social acceptance and rejection experienced by the main character in the Stargirl novel. This study aimed to reveal the representation of social acceptance categories that occured towards the main character and also to reveal the form of social rejection experienced by the main character in the novel “Stargirl”. A qualitative descriptive research method was used, incorporating supporting quotes from the novel and other sources. Through a psychological approach, the researcher examined the categories of social acceptance from Hurlock and form of social rejection by Baumeister and Leary. The researcher found the results of the study that in the Stargirl novel, there was evidence of social acceptance in the form of star, accepted, and fringer experienced by the main character. In addition, the researcher found that not only social acceptance, social rejection of the main character Stargirl was found in the form of active, passive, other or verbal, and social or peer rejection.